Práticas docentes e o uso das TIC : E-Proinfo e o curso “Redes de Aprendizagem” - Evangelista, Edilene Quirino Neiva (2017)
This work is the result of a research of Master’s Education from Universidade Federal de Mato Grosso, having as a main objective to comprehend whether the course Redes de Aprendizagem (RA) offered by the Proinfo Integrado, through the continued training, can influence or not on the pedagogical practices of teachers and register how the use of Information and Communication Technologies is at the school. The subjects are 14 (fourteen) teachers of Elementary Education crowded through Secretaria de Estado de Educação de Mato Grosso (SEDUC/MT), that in 2014, made the continued training with the option in educational technology. Such formation was directed by Centro de Formação e Atualização dos Profissionais da Educação Básica do Estado de Mato Grosso (CEFAPRO/MT) in the pole of Tangará da Serra/MT, and the achievements reports of the course and it respectives activities while that formation were made using the e-Proinfo platform. The locus of research are three: Escola Estadual Luiz Frutuoso da Silva – Sapezal, Escola Estadual Francisca de Souza Alencar – Nova Olímpia e Escola Estadual Vereador Bento Muniz – Tangará da Serra. It is a study that shows a qualitative inquiry, using the exploratory-descriptive method and the methodological option is based on the Denzin and Lincoln’s conceptions (2006). As a data collecting instruments were made the following actions: documental analysis using the collection of CEPAFRO/MT, the application of questionnaires to the management of the three schools mentioned before, the 14 (fourteen) subjects and finally, the participant observation at the Unidade Escolar in which they act. The result of the research revealed some practices that we classify under three dimensions: of the administrative use, being this most effective and frequent in the school used for the planning of the classes and reports in the system SigEduca da SEDUC/MT; of classroom uses or in environments used for that, in which the use is registered in a more individual way for the development of projects or in the utilization of Laboratório de Informática Educativa (LIED) and not as a recurring practice. The last dimension, which is an attempt incorporation of the school in more extensive context, where it shows itself, wants to be seen and it is done through Facebook and the blog. The technological resource more used by our subjects in theirs pedagogical practices is Data Show and there is a general claim in terms of the operational system LINUX installed at LIEDs. According to the information obtained with the realization of this research, we can point out that exists a way to be traveled in relation to the ICT use, being that there is a lack of continued training in educational technology or even the quality offered by those technologies that can be pointed out as an hint of not use, as well as, just the presence of technological resources at the school that do not guarantee the effective use of them in the teaching practices of teachers, even though there is an investment by the public policies, which is not a decisive factor for the effective use of ICT.